Social Image of Nursing. An Integrative Review about a Yet Unknown Profession - López-Verdugo, Macarena; Ponce-Blandón, Jose Antonio; López-Narbona, Francisco Javier; Romero-Castillo, Rocío; Guerra-Martín, María Dolores (Nursing reports (Pavia, Italy), 2021)
Background: Nursing is a discipline on which stereotypes have persisted throughout its history, considering itself a feminine profession and subordinated to the medical figure, without its own field of competence. All this leads to an image of the Nursing Profession that moves away from reality, constituting a real, relevant and high-impact problem that prevents professional expansion, and that has a direct impact on social trust, the allocation of resources and quality of care, as well as wages and professional satisfaction. The aim of this review was to identify and publicize the published material on the social image of Nursing, providing updated information about the different approaches to the subject. Methods: An integrative review of the literature has been made from primary sources of information published from 2010 to 2020. For this, the databases CINAHL, Scopus, SciELO, Dialnet and Cuiden have been consulted. Results: In total, 17 articles have been included in the review, with qualitative, quantitative, and even bibliographic reviews performed in countries such as Spain, Egypt, Argentina, Iran, Venezuela, Turkey, United Kingdom, and Australia. The results of those papers mostly showed that society has misinformation about the functions performed by nursing professionals, which is based on myths and stereotypes. Conclusions: Nursing is a profoundly unknown and invisible profession, as society continues without recognizing its competence, autonomy and independence.